Neurobiology of inflammation-associated anorexia - Gautron, Laurent; Laye, Sophie (Frontiers in Neuroscience, 2010)
Compelling data demonstrate that inflammation-associated anorexia directly results from the action of pro-inflammatory factors, primarily cytokines and prostaglandins E2, on the nervous system. For instance, the aforementioned pro-inflammatory factors can stimulate the activity of peripheral sensory neurons, and induce their own de novo synthesis and release into the brain parenchyma and cerebrospinal fluid. Ultimately, it results in the mobilization of a specific neural circuit that shuts down appetite. The present article describes the different cell groups and neurotransmitters involved in inflammation-associated anorexia and examines how they interact with neural systems regulating feeding such as the melanocortin system. A better understanding of the neurobiological mechanisms underlying inflammation-associated anorexia will help to develop appetite stimulants for cancer and AIDS patients.